2019
DOI: 10.1111/cgf.13619
|View full text |Cite
|
Sign up to set email alerts
|

Deep Fluids: A Generative Network for Parameterized Fluid Simulations

Abstract: This paper presents a novel generative model to synthesize fluid simulations from a set of reduced parameters. A convolutional neural network is trained on a collection of discrete, parameterizable fluid simulation velocity fields. Due to the capability of deep learning architectures to learn representative features of the data, our generative model is able to accurately approximate the training data set, while providing plausible interpolated in‐betweens. The proposed generative model is optimized for fluids … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
267
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(277 citation statements)
references
References 40 publications
0
267
0
Order By: Relevance
“…In the same way that numerical relativity simulations of BBH mergers have been critical for the detection and characterization of these sources with GW observations, numerical relativity simulations of BNS and NSBH mergers are critical to get insights into the physical processes that may lead to the production of electromagnetic and astro-particle counterparts, and to better interpret MMA observations 67 . These modeling efforts do not currently benefit from DL, but recent studies have suggested the possibility to improve the efficiency and robustness of simulations, enabling the inclusion of detailed microphysics [68][69][70][71][72] , and a significance increase in the speed with which partial different equations are solved 73,74 .…”
Section: Real-time Detection Of Gws and Neutrinosmentioning
confidence: 99%
“…In the same way that numerical relativity simulations of BBH mergers have been critical for the detection and characterization of these sources with GW observations, numerical relativity simulations of BNS and NSBH mergers are critical to get insights into the physical processes that may lead to the production of electromagnetic and astro-particle counterparts, and to better interpret MMA observations 67 . These modeling efforts do not currently benefit from DL, but recent studies have suggested the possibility to improve the efficiency and robustness of simulations, enabling the inclusion of detailed microphysics [68][69][70][71][72] , and a significance increase in the speed with which partial different equations are solved 73,74 .…”
Section: Real-time Detection Of Gws and Neutrinosmentioning
confidence: 99%
“…To ensure that a user's intention is reflected in the generation process, studies have typically used a painting interaction (e.g., brushing, copy, and paste), which allows users to adjust the output appearance with user drawings while preserving the realism of the generated results . For physics simulation, machine learning approaches have been attracting worldwide attention because these systems can construct plausible results faster than resimulating (or synthesizing) new data . For example, tempoGAN introduced a super‐resolution method to generate an arbitrary high‐resolution fluid result (highly detailed and temporally coherent features) from a low‐resolution input .…”
Section: Related Workmentioning
confidence: 99%
“…22 For physics simulation, machine learning approaches have been attracting worldwide attention because these systems can construct plausible results faster than resimulating (or synthesizing) new data. 23 For example, tempoGAN introduced a super-resolution method to generate an arbitrary high-resolution fluid result (highly detailed and temporally coherent features) from a low-resolution input. 24 In this study, we utilized an interactive machine learning approach for 2D vector field generation in flow design problems.…”
Section: Figurementioning
confidence: 99%
“…Recently, machine learning (ML) tools, especially artificial neural networks (ANNs) have been playing a significant role in different fields of science and engineering [88][89][90]. The merits of machine learning algorithms have been demonstrated for prototypical fluid mechanics applications, including flow modeling, reconstruction, and control [91][92][93][94][95]. This is due to their superior capability to identify the linear and non-linear maps between input and output data as well as extracting underlying patterns [96][97][98][99].…”
mentioning
confidence: 99%